Reference values for quantitative parameters in renal scintigraphy with Tc-99m-MAG3 - Eilsberger, Friederike; Reiber, Constantin; Luster, Markus; Librizzi, Damiano; Pfestroff, Andreas; Verburg, Frederik A. (Nuklearmedizin - NuclearMedicine, 2020)
Background Reference values are the basis for an increase of standardisation and examiner independence, and thus an improvement in the inter-institutional comparability. However for renal Mercaptoacetyltriglycin (MAG3)-scintigraphy the establishment of such values however did not find its way into clinical routine despite the convincing advantages.Aim The aim was to establish reference values for the decisive quantitative parameters of MAG3 renal scintigraphy. The reference values should help to significantly improve and facilitate the interpretation of the examination results in everyday clinical practice.Methods We retrospectively evaluated all MAG3 renal scintigraphies performed in the Department of Nuclear Medicine, University Hospital Marburg between 01/2014 and 08/2017. The total sample of non-pathological renal scintigrafies included 247 patients aged between 25 days and 88 years. All investigtions were performed according to the present guidelines of the German Association for Nuclear Medicine. We analysed the ratio from pulse count rate after 20 minutes/Time (T) max and the Tmax separately.Results Reference values for the Tmax and 20 min/T(max) count ratio of the MAG3 renal scintigraphy were defined for all adults over 18 years and divided by age catogories. For children aged 0–0.5 years and 0.5–2 years reference values for Tmax were defined.Conclusion The results show a high degree of consistency with the reference values screened out in previous studies. This underlines the reliability of the reference values as a diagnostic tool in clinical application. The defined values are clinically feasible and promise a simplified and improved interpretation of the MAG3 renal scintigraphy.
Keywords: renal scintigraphy; MAG3; reference values